Difficult laryngoscopy and tracheal intubation: observational study - Andrade,Rebeca Gonelli Albanez da Cunha (2018)
Abstract Introduction: Since anesthesia complications associated with unexpected difficult airway are potentially catastrophic, they should be avoided. The modified Mallampati test and jaw-thrust maneuver enable the identification of difficult airway. The aim of this study was to associate the modified Mallampati test and the jaw-thrust maneuver with laryngoscopy (Cormack–Lehane) in an attempt to identify a better predictor of difficult airway in an adult population undergoing elective surgery. Method: A cross-sectional study in which 133 adult patients undergoing elective surgery requiring tracheal intubation were analyzed. The accuracy and specificity of the modified Mallampati test and jaw-thrust maneuver were assessed by correlating them with difficult laryngoscopy (Cormack–Lehane Degrees 3 and 4). Results: In the 133 patients evaluated the difficult intubation rate found was 0.8%; there was association between the two predictive tests proposed (p = 0.012). The values of 94.5% for specificity and 95.4% for accuracy were found for the jaw-thrust maneuver and for the modified Mallampati test, the values found were 81.1% and 81.2%, respectively. Kappa agreement identified a result of 0.240 between jaw-thrust maneuver and Cormack–Lehane, which was considered reasonable. On the other hand, a poor agreement (κ = 0.06) was seen between modified Mallampati test and Cormack–Lehane test. Conclusion: The jaw-thrust maneuver presented superior accuracy and agreement than the modified Mallampati test, showing the ability to identify a difficult airway. It is necessary to emphasize the association of tests in the evaluation of patients, emphasizing their complementarity to minimize the negative consequences of repeated laryngoscopies.